Marketing Activities and Perceptions towards Domestic Tourism and Domestic Tourists (A Case Of Accommodation Providers In S?moa) - Samau, Bernadette (British Journal of Marketing Studies, 2016)
Effective Marketing strategies and techniques have contributed to the competitive survival and development of many tourism operators worldwide. Given S?moa’s geographic isolation as a holiday destination, marketing activities should aim to target both international and domestic tourists. However, the S?moan Government tends to focus predominantly on the promotion of international tourism. Domestic tourism and travel by local tourists is an area neglected by some tourism operators and domestic marketing and promotional activities are limited. This paper presents the results of a small scale study designed to investigate marketing activities, perceptions towards domestic tourism and the idea of locals as tourists from the view point of operators in the Accommodation Sector. Convenience Sampling identified a sample of 50 Accommodation providers for the study. The percentage method analysis confirms the existence of marketing activities. In spite of this, existing marketing activities are primarily designed to target international tourists. Talanoa Research Method (TRM) was used to conduct in-depth interviews. Thematic Analysis highlighted some interest among operators to invest in marketing activities however financial constraints, high preference for international tourists and personal motives limited interest and investment in marketing activities to target local tourists